ELECTROKINETIC SPONTANEOUS POLARIZATION IN POROUS MEDIA: PETROPHYSICS AND NUMERICAL MODELLING - Titov K.; Ilyin Yu.; Konosavski P.; Levitski A. (My University, 2002)
The behaviour of streaming potential is directly related to movement of groundwater. The responses for typical subsurface flows are modelled to investigate possibilities of spontaneous polarization (SP) when performing quantitative data interpretation. The physical properties of geomaterials related to streaming potential are described. A magnitude range of streaming current coefficient is assessed for geomaterials and found to be from −10−10 to −10−8 A/Pa m, depending on water salinity and rock composition. The electrical sources of SP caused by groundwater flow in saturated media are theoretically described. It is shown that SP is completely defined by three types of electrical sources situated (1) on boundaries where water enters or quits porous media, (2) in areas with transient regime, and (3) on the boundaries of rocks with different properties (hydraulic conductivity, streaming current coefficients and electrical conductivity). A 2D-computer program based on the method of finite difference was created to provide numerical successive modelling of both groundwater flow and SP. Using Sill's [Geophysics 48 (1983) 76] approach, first the water heads are calculated. Then, electrical sources of SP are obtained on the basis of the calculated heads and coefficient of streaming current. Finally, the SP is obtained on the basis of calculated electrical sources and subsurface electrical conductivity. Numerical examples illustrating SP responses of infiltration, of barrage with different electrical conductivity, and of well pumping are discussed. Field data obtained at the site containing the dam between superficial artificial reservoir and the river are interpreted on the basis of numerical modelling. The discussed method can be mainly used for additional calibration of groundwater flow models.